Adalimumab and Infliximab Impair SARS-CoV-2 Antibody Responses: Results from a Therapeutic Drug Monitoring Study in 11 422 Biologic-Treated Patients. (2nd September 2021) - Chanchlani, Neil; Lin, Simeng; Chee, Desmond; Hamilton, Benjamin; Nice, Rachel; Arkir, Zehra; Bewshea, Claire; Cipriano, Bessie; Derikx, Lauranne A A P; Dunlop, Allan; Greathead, Louise; Griffiths, Rachel L; et al.
Abstract: Background and Aims: Infliximab attenuates serological responses to SARS-CoV-2 infection. Whether this is a class effect, or if anti-tumour necrosis factor [anti-TNF] level influences serological responses, remains unknown. Methods: Seroprevalence and the magnitude of SARS-CoV-2 nucleocapsid antibody responses were measured in surplus serum from 11 422 (53.3% [6084] male; median age 36.8 years) patients with immune-mediated inflammatory diseases, stored at six therapeutic drug monitoring laboratories between January 29 and September 30, 2020. Data were linked to nationally held SARS-CoV-2 PCR results to July 11, 2021. Results: Rates of PCR-confirmed SARS-CoV-2 infection were similar across treatment groups. Seroprevalence rates were lower in infliximab- and adalimumab- than vedolizumab-treated patients (infliximab: 3.0% [178/5893], adalimumab: 3.0% [152/5074], vedolizumab: 6.7% [25/375], p  = 0.003). The magnitude of SARS-CoV-2 reactivity was similar in infliximab- vs adalimumab-treated patients (median 4.30 cut-off index [COI] [1.94–9.96] vs 5.02 [2.18–18.70], p  = 0.164), but higher in vedolizumab-treated patients (median 21.60 COI [4.39–68.10, p  < 0.004). Compared to patients with detectable infliximab and adalimumab drug levels, patients with undetectable drug levels [<0.8 mg/L] were more likely to be seropositive for SARS-CoV-2 antibodies. One-third of patients who had PCR testing prior to antibody testing failed to seroconvert, all were treated with anti-TNF. Subsequent positive PCR-confirmed SARS-CoV-2 was seen in 7.9% [12/152] of patients after a median time of 183.5 days [129.8–235.3], without differences between drugs. Conclusion: Anti-TNF treatment is associated with lower SARS-CoV-2 nucleocapsid seroprevalence and antibody reactivity when compared to vedolizumab-treated patients. Higher seropositivity rates in patients with undetectable anti-TNF levels support a causal relationship, although confounding factors, such as combination therapy with a immunomodulator, may have influenced the results.